Effect of surface modification on nano-diamond particles for surface and thermal property of UV-curable hybrid coating - KAHRAMAN, MEMET VEZİR (ELSEVIER SCIENCE SA, 2016)
Surface modification is a common and efficient way to improve the compatibility of nano-diamond particles (NDs) with various matrixes. In this study we report the modification of NDs with functional groups which are UV reactive. This modification promotes the covalent bonding of NDs to the UV-curable matrix by crosslinking photo-polymerization and thus homogeneous composites are formed. NDs surface was photografted with polyethylene glycol acrylate (PEGA) to produce hydroxyl groups. Hydroxyl functionalized NDs/PEGA were silanized using hydrolyzed 3-(Methacryloxy)propyl trimethoxysilane (hydMEMO) in order to develop an improved dispersion and interaction between interfaces in composites. UV-curable resin formulation was prepared by mixing the silane modified NDs, hydrophobic aromatic urethane acrylate, N-vinyl pyrrolidone, 2-ethylhexyl acrylate, trimethylolpropane triacrylate (TMPTA) and photoinitiator. The amount of Si-NDs/PEGA in the hybrid composites were varied from 0 wt% to 5 wt%. The morphology, thermal endurance and surface properties of hybrid composites were characterized by scanning electron microscopy (SEM), ATR-FTIR, thermogravimetric analysis (TGA), atomic force microscope (AFM) and contact angle. In addition, spatial distribution and amount of silane was determined by elemental mapping. FTIR results showed that the photografted NDs (NDs/PEGA), silane modified NDS/PEGA (Si-NDs/PEGA) and hybrid composites were successfully prepared. SEM and AFM results dictated that the Si-NDs/PEGA was homogeneously dispersed in the composite matrix and they showed good compatibility. Energy dispersive spectrometer (SEM-EDS) elemental mapping results show that the elements C, O and Si are uniformly spread on the surface of the ND particles. In summary, the silanization can improve the dispersion of NDs and the interfacial adhesion between Si-NDs/PEGA and UV curable formulation so as to enhance the thermal properties of hybrid composites. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Photograft; Nano-diamond; UV-curable hybrid composites; Surface modification; NATURAL-RUBBER COMPOSITES; CARBON NANOTUBES; CHEMICAL FUNCTIONALIZATION